2005
DOI: 10.1111/j.1365-2036.2006.02737.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis: levofloxacin‐based rescue regimens after Helicobacter pylori treatment failure

Abstract: SUMMARY BackgroundA quadruple therapy has been generally recommended as rescue regimen for Helicobacter pylori eradication failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
256
5
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(284 citation statements)
references
References 38 publications
12
256
5
11
Order By: Relevance
“…3,4 Our success rate, however, is significantly higher compared to their results. It would be pertinent to know the current level of resistance to levofloxacin in Spain.…”
contrasting
confidence: 50%
“…3,4 Our success rate, however, is significantly higher compared to their results. It would be pertinent to know the current level of resistance to levofloxacin in Spain.…”
contrasting
confidence: 50%
“…Three meta-analysis confirm that associating a standard dose of proton pump inhibitor, twice a day, amoxicillin 1.0 g twice a day and levofloxacin 500 mg once daily for 10 days achieves eradication rates of around 80% (74,122,179) . Although widely used in Brazil there are no validation studies among us.…”
Section: Statement 30mentioning
confidence: 79%
“…Fluoroquinolones have been suggested as alternative drug but generally the results of fluoroquinolone triple therapy was less than 90% (Gisbert and Morena, 2006;Graham and Shiotani, 2012). In addition, recent studies have demonstrated that longer duration with 14-day fluoroquinolone triple therapy provided treatment success of 95% (Miehlke et al, 2011).…”
Section: Discussionmentioning
confidence: 99%